2009
DOI: 10.1192/bjp.195.52.s20
|View full text |Cite
|
Sign up to set email alerts
|

First-generation antipsychotic long-acting injections v. oral antipsychotics in schizophrenia: Systematic review of randomised controlled trials and observational studies

Abstract: The results are variable and inconclusive. Some evidence suggests that FGA-LAIs may improve outcome compared with oral antipsychotics. Methodological issues may partly explain the variable results. Selective recruitment in RCTs and lack of randomisation in observational studies are biases against LAIs, whereas regression to the mean in mirror-image studies favours LAIs. In terms of future research, a long-term pragmatic RCT of an FGA-LAI against an oral antipsychotic, in patients with problematic adherence, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
80
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 51 publications
0
80
0
2
Order By: Relevance
“…Therefore, long-acting depot formulations are often recommended for individuals who are known to have patterns of nonadherence to oral antipsychotic medication. 5,6 However, the findings in the clinical literature regarding the comparative effectiveness of depot versus oral antipsychotics in schizophrenia have been inconsistent. [7][8][9] These findings have challenged the field to consider the proper role of long-acting depot therapy.…”
mentioning
confidence: 99%
“…Therefore, long-acting depot formulations are often recommended for individuals who are known to have patterns of nonadherence to oral antipsychotic medication. 5,6 However, the findings in the clinical literature regarding the comparative effectiveness of depot versus oral antipsychotics in schizophrenia have been inconsistent. [7][8][9] These findings have challenged the field to consider the proper role of long-acting depot therapy.…”
mentioning
confidence: 99%
“…6 Observational studies demonstrate many benefits of long-acting injectable medications, such as reducing total number of days in the hospital and better functional outcomes. 7,8 Long-acting injectable antipsychotics are not often prescribed in patients with FEP 9 despite high nonadherence rates for oral medications and concurrent relapse of psychosis 10 (this is likely due to stigma associated with long acting injectable medications, as they are often seen as treatment of last resort).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 a systematic review of evidence comparing FGA oral antipsychotics and FGA LAIs by Haddad et al proved inconclusive, with contradictory evidence found during review. 8 Adams et al in a 2001 meta-analysis of RCTs showed no difference in relapse or tolerability between oral and LAI FGAs. 8,9 Very few direct comparisons of first-and second-generation LAIs exist.…”
mentioning
confidence: 99%
“…8 Adams et al in a 2001 meta-analysis of RCTs showed no difference in relapse or tolerability between oral and LAI FGAs. 8,9 Very few direct comparisons of first-and second-generation LAIs exist. Those that have been published continue to suggest that the differences are less clear than those proposed when SGAs were brought to market.…”
mentioning
confidence: 99%